Increasing The Family Law Aspects Understanding For Depok City Community - Heru Sugiyono; Suprima Suprima; Aji Lukman Ibrahim (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Family law is part of the clump of civil law that discusses the problems of civil relations in a family, including marriage, divorce, inheritance, and so on. The purpose of this service is to provide an understanding of aspects of family law for the people of Depok. The method used in the implementation of the service is to provide counseling to the people of Kampung Pulo, Leurahan Beji Depok through the media zoom meeting. The results of community service show that some people in the city of Depok, especially in Kampung Pulo, Beji Depok Village, still do not understand the efforts that must be made when problems occur related to family law. Community Service Program activities are very helpful for the people of Depok to better understand the efforts that must be made when problems occur in family law.